The Application Of Experimental Methods In Improving The Understanding Of The Concept Of Substance Changes In Grade V Elementary Students - Nurhayati Nurhayati; Wahyu Kurniawati (Sean Institute, 2024)
The process of learning activities is an important factor in determining the success of students' learning achievements. Therefore, teachers must be able to sort and choose and determine learning approaches that are appropriate to the learning material and student characteristics in the learning process and learning objectives. The application of an appropriate learning approach is assumed to influence students' physics learning achievement. The aim of this researcher is to find out how teachers apply experimental models to increase understanding of the concept of changes in substances for class V students in one of the elementary schools in Bajing Village, Kroya District. This research is a qualitative research. The population of this study was a fifth grade teacher at one of the elementary schools in Bajing village, Kroya subdistrict. This data collection technique uses interviews with one of the class V teachers at one of the elementary schools in Bajing village, Kroya sub-district. Based on the results of this research, the suitability of learning shows that the teacher uses experimental methods on material changes in substances so that students understand it better. Based on the results of the analysis and discussion, it can be concluded that learning using the experimental method can increase students' understanding of the material on changes in substances. This can be seen from the students' ability to carry out the experiments given.